Recent Advances in Cognitive Behavioral Therapy For Digestive Disorders and the Role of Applied Positive Psychology Across the Spectrum of GI Care. Issue 7 (August 2019) - Feingold, Jordyn; Murray, Helen B.; Keefer, Laurie
Abstract : Background: Although cognitive behavior therapies (CBTs) have shown great promise in the reduction of symptom burden from as well as anxiety around various gastrointestinal (GI) disorders, there are substantial issues involving the scalable delivery of such interventions within the clinical setting of a gastroenterology practice, leaving most patients without access to psychological care. Goals: This paper discusses the application of positive psychology principles and techniques for adoption by various GI providers to initiate early, effective psychological care for patients with GI disorders, saving CBTs for more complex cases. Study/Results: Authors provide a comprehensive framework of patient well-being known as REVAMP, which is consistent with CBT principles, and elaborate on research and interventions that can be adopted within the gastroenterology practice setting. Building positive resources can bolster patients with GI disorders against comorbid psychological and psychiatric distress. Conclusions: Positive psychology interventions can be implemented within gastroenterology practice. Research is necessary to evaluate the efficacy and acceptability of positive psychology interventions among patients with different digestive disorders and baseline psychological characteristics, as well as the feasibility of administration by different clinicians in the gastroenterology practice setting.